Design and optimization of new simulated moving bed plants - Azevedo,D. C. S. (2006)
The simulated moving bed (SMB) technology has attracted considerable attention for its efficiency as a chromatographic adsorptive separation. It has been increasingly applied to the separation of binary mixtures with low separation factors, namely to separate isomers. Although quite a vast amount of information has been published concerning the simulation and design of operating conditions of existing SMB plants, fewer works have addressed the question of design and optimisation of geometric parameters and operating conditions of a new adsorber, especially when mass transfer resistances are significant. The present work extends an algorithm developed elsewhere to design SMB equipment and optimize its operating conditions and applies it to the case of fructose-glucose separation using a cation-exchange resin as stationary phase in order to obtain nearly pure fructose in the extract and glucose in the raffinate. The constraints were set as 99% purity for both products. The objective function was chosen to be the adsorbent productivity. The algorithm attempted to find the minimum column lengths for increasing throughputs, which met the required purity constraint. Then, the best construction parameters and operating conditions were chosen as those for which the adsorbent productivity was maximum. The effects of the safety margins applied on the velocity ratios in sections 1 and 4 were examined and a heuristic rule for optimum eluent flowrate was derived. The effect of the purity requirements was also investigated. Finally, the calculated optimal operating points, in terms of flowrate ratios in SMB sections 2 and 3, were analysed in the frame of the equilibrium theory. Sound coherence was verified, which confirmed the accuracy and adequacy of the extended algorithm for the design and optimisation of a SMB adsorber with strong mass transfer effects.